Atypical Melanocytic Proliferations: A Review of the Literature. Issue 2 (February 2018) - Ensslin, Courtney J.; Hibler, Brian P.; Lee, Erica H.; Nehal, Kishwer S.; Busam, Klaus J.; Rossi, Anthony M.
Abstract : BACKGROUND: Ambiguous histopathologic diagnoses represent a challenge for clinicians because of a lack of definitive diagnosis and related uncertainty about management. OBJECTIVE: To review the literature on atypical melanocytic proliferations and detail synonymous terms, epidemiology, diagnostic work-up, histopathology, treatment, and prognosis. METHODS: Databases from PubMed and Web of Science were searched for articles related to atypical melanocytic proliferations. RESULTS: Intraepidermal melanocytic proliferations with features worrisome for possible melanoma in situ (MIS) are generally excised as for MIS. Reported rates of upstaging of such cases to invasive melanoma on review of the excision are very low. Because invasion, lymph node spread, and metastasis can occur in atypical melanocytic lesions with a thick intradermal component, these are often treated as for malignant melanoma. CONCLUSION: Because the diagnosis dictates treatment, it is incumbent to establish a diagnosis as definitive as possible, obtaining second or third opinions and using ancillary studies when appropriate. When the diagnosis remains uncertain, it is difficult to provide guidelines for treatment. Clinical care decisions for patients with an uncertain diagnosis are best done on a case-by-case basis weighing probabilities of adverse outcomes against potential benefits and risks from various treatment options.